2018
DOI: 10.1155/2018/8719624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Visible Light Curing Capacity of Polycaprolactone Acrylate

Abstract: Polycaprolactone (PCL) is drawing increasing attention in the field of medical 3D printing and tissue engineering because of its biodegradability. This study developed polycaprolactone prepolymers that can be cured using visible light. Three PCL acrylates were synthesized: polycaprolactone-530 diacrylate (PCL530DA), glycerol-3 caprolactone triacrylate (Glycerol-3CL-TA), and glycerol-6 caprolactone triacrylate (Glycerol-6CL-TA). PCL530DA has two acrylates, whereas Glycerol-3CL-TA and Glycerol-6CL-TA have three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Visible light-based SLA overcomes issue as the increase in the light intensity or PI concentration will not impact the cells as much, enhancing the printing quality and integrity. 117,118 Lim et al 117 demonstrated a novel SLA technique that produced enhanced print qualities using a visible light-sensitive PI with high intensities, the PI was ruthenium (Ru)/ sodium persulfate. Immediate cell viability using this system was higher when UV-sensitive Irgacure 2959 was used, which is the least toxic PI among the UV-sensitive options.…”
Section: Additive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible light-based SLA overcomes issue as the increase in the light intensity or PI concentration will not impact the cells as much, enhancing the printing quality and integrity. 117,118 Lim et al 117 demonstrated a novel SLA technique that produced enhanced print qualities using a visible light-sensitive PI with high intensities, the PI was ruthenium (Ru)/ sodium persulfate. Immediate cell viability using this system was higher when UV-sensitive Irgacure 2959 was used, which is the least toxic PI among the UV-sensitive options.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Visible light-based SLA overcomes issue as the increase in the light intensity or PI concentration will not impact the cells as much, enhancing the printing quality and integrity. 117,118…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“… 75 To eliminate the damaging effects of UV exposure on cells, visible light-sensitive photoinitiators can be utilized. Examples of such initiators are lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP), 76 camphorquinone, 23 and eosin Y. 77 Resolution depends on the stereolithographic technology, for example, two-photon SLA has higher printing resolution than single-photon SLA.…”
Section: Techniquesmentioning
confidence: 99%
“…Glycerol-caprolactone oligomers containing 1 or 2 caprolactone units were prepared by the ROP of ε-caprolactone with glycerol, at 130 • C, in the presence of stannous octoate and were further functionalized with acryloyl chloride (N(CH 3 ) 3 , THF, N 2 atmosphere, dark) [233]. The obtained polymers were low-viscosity liquids that were photopolymerized in the presence of a photo-initiator (camphorquinone) and a co-initiator (dimethylaminoethyl methacrylate) by exposure to 470 nm blue LED light.…”
Section: Functionalized Polyglycerol/poly(ε-caprolactone) Copolymers mentioning
confidence: 99%